Bonhoeffer and Reformed Christology: Towards a Trinitarian Supplement. Issue 1 (April 2014) - Holmes, Christopher R.J.
In this article, I examine Bonhoeffer's aversion to the Reformed extra Calvinisticum, namely that the extra undermines a real incarnation, the sense in which God is "wholly there." However, what Bonhoeffer did not supply is an account of what qualifies Jesus Christ to be the "God-human" and the "human-God." This is where, I argue, a strong trinitarian supplement is necessary. Bonhoeffer's rather undeveloped trinitarian theology undermined a full articulation of who it is who is said to be wholly there. Without an account of Christ's origin in relationship to the Father, Bonhoeffer's christology was hamstrung, unable to fully realize the full power of its immensely salutary efforts to be transparent to Christ's interpretation of himself to us.